A Working Hypothesis for Broadening Framework Types of Zeolites in Seed-Assisted Synthesis without Organic Structure-Directing Agent - Itabashi, Keiji; Kamimura, Yoshihiro; Iyoki, Kenta; Shimojima, Atsushi; Okubo, Tatsuya (Journal of the American Chemical Society, 2012)
Recent research has demonstrated a new synthesis route to useful zeolites such as beta, RUB-13, and ZSM-12 via seed-assisted, organic structure-directing agent (OSDA)-free synthesis, although it had been believed that these zeolites could be essentially synthesized with OSDAs. These zeolites are obtained by adding seeds to the gels that otherwise yield other zeolites; however, the underlying crystallization mechanism has not been fully understood yet. Without any strategy, it is unavoidable to employ a trial-and-error procedure for broadening zeolite types by using this synthesis method. In this study, the effect of zeolite seeds with different framework structures is investigated to understand the crystallization mechanism of zeolites obtained by the seed-assisted, OSDA-free synthesis method. It has been found that the key factor in the successful synthesis of zeolites in the absence of OSDA is the common composite building unit contained both in the seeds and in the zeolite obtained from the gel after heating without seeds. A new working hypothesis for broadening zeolite types by the seed-assisted synthesis without OSDA is proposed on the basis of the findings of the common composite building units in zeolites. This hypothesis enables us to design the synthesis condition of target zeolites. The validity of the hypothesis is experimentally tested and verified by synthesizing several zeolites including ECR-18 in K–aluminosilicate system.